RETHINKING FOOD DIPLOMACY: A CRITICAL REVIEW OF INDONESIA'S RICE DIPLOMACY - Fitri Fatharani; Arie Fitria; Irsyaad Suharyadi (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This paper presents a critical literature review on Indonesia’s rice surplus diplomacy within the framework of South–South Cooperation (SSC). Drawing from nine key studies, the literature review identifies three thematic clusters: food diplomacy in the Global South, critics of SSC solidarity discourse, and Indonesia’s rice surplus as an instrument of foreign policy. While SSC emphasizes equality and mutual benefit, emerging literature reveals tensions between rhetorical commitments to solidarity and the strategic, state-centric practices of donor countries. Indonesia’s case exemplifies how rice surplus has evolved from a symbol of domestic achievement to a soft power instrument, used to assert regional leadership amid global food crises. However, this transformation also exposes gaps in regional governance and risks reinforcing power asymmetries under the guise of humanitarianism. The review calls for a rethinking of SSC and food-based diplomacy, advocating for inclusive mechanisms that balance national interests with collective resilience.